The brain antigen-specific B cell response correlates with glatiramer acetate responsiveness in relapsing-remitting multiple sclerosis patients - Rovituso, Damiano M.; Duffy, Cathrina E.; Schroeter, Michael; Kaiser, Claudia C.; Kleinschnitz, Christoph; Bayas, Antonios; Elsner, Rebecca; Kuerten, Stefanie (Scientific Reports, 2015)
B cells have only recently begun to attract attention in the immunopathology of multiple sclerosis (MS). Suitable markers for the prediction of treatment success with immunomodulatory drugs are still missing. Here we evaluated the B cell response to brain antigens in n = 34 relapsing-remitting MS (RRMS) patients treated with glatiramer acetate (GA) using the enzyme-linked immunospot technique (ELISPOT). Our data demonstrate that patients can be subdivided into responders that show brain-specific B cell reactivity in the blood and patients without this reactivity. Only in patients that classified as B cell responders, there was a significant positive correlation between treatment duration and the time since last relapse in our study. This correlation was GA-specific because it was absent in a control group that consisted of interferon-ß (IFN-β)-treated RRMS patients (n = 23). These data suggest that GA has an effect on brain-reactive B cells in a subset of patients and that only this subset benefits from treatment. The detection of brain-reactive B cells is likely to be a suitable tool to identify drug responders.
CRIS-Team Scopus Importer:2022-08-05